Examining the Role of CSR and Technological Readiness in the Intelligent Transformation of SMEs in Northern Province, Sri Lanka - Sathana, V. (University of Sri Jayewardenepura, 2025)
Purpose: The purpose of this research is to find out the impact of external and internal factors on the intelligent technology readiness of SMEs and the moderation effect of corporate social responsibility (CSR) on the relationship between external and internal factors and intelligent technology readiness. Design/methodology/approach: Data were collected from owners of the SMEs. A convenient sampling technique was applied to select the respondents. A Total of 143 valid responses from SMEs in various industries participated in this survey. Data were analyzed by using confirmatory factor analysis (CFA) and Structure Equation Modeling (SEM). Findings: The findings revealed that internal and external factors significantly influence the intelligent technology readiness of SMEs. Furthermore, corporate social responsibility (CSR)negatively moderates the relationship between external factors and the intelligent technology readiness of SMEs. However, CSR does not moderate the relationship between internal factors and the intelligent technology readiness of SMEs. Originality: This study addresses a critical research gap by empirically testing Wang et al.’s (2022) conceptual model within the context of the SME sector, specifically in a post-conflict, resource-constrained region such as Northern Sri Lanka. This paper confirms that external factors should be considered highly for technology readiness and internal factors should be handled to incorporate intelligent technology transformation. However, corporate social responsibility is not taken high consideration by the SME sector. Implications: The study implies that SME owners understand the intelligent technology need and implement internal changes in management practice, upskill employees, and utilize external opportunities to sustain in a competitive and tech-driven market. The intelligent technology application is vital for the economic growth of the region.
Keywords: External Factors; Internal Factors; Intelligent Transformation; SMEs; Technology Readiness